Isis en occident : actes du IIème Colloque international sur les études isiaques, Lyon III 16-17 mai 2002 - Bricault, Laurent. (Religions in the Graeco-Roman World, 2004)
In this volume, 16 contributions by specialists of political and religious history of Antiquity give a precious general overview of the diffusion of Egyptian cults in the West. The first part gives a very precise survey of the diffusion of Egyptian cults in the western Roman world, while the second part of the book is devoted to special fields usually considered as subsidiary (numismatics, lychnology, gemmology), but in fact essential for a better understanding of the success of the Isiac cults in the Graeco-Roman world between 330 BC and 400 AD.